Liver enzymes and biochemical function tests in t2dm: impact of duration, glycemic control and some other co-variables - Al-Naemi, Amjad Hazim (Vojenské zdravotnické listy, 2024)
Background and Purpose: T2DM is the most common cause of end- stage liver diseases, and different mechanisms contribute to diabetic hepatopathy's wide spectrum presentation. In this study, we aimed to identify abnormalities in liver function tests (LFTs) for a group of Iraqi T2DM patients, determine their prevalence, and investigate the influence of some independent co-variables (duration of DM, HbA1c, BMI, age, and gender). Methods: This case-control study enrolled 43 T2DM patients alongside 40 healthy, age- and sex- matched non-diabetic subjects. After overnight fasting, blood was collected, and fasting plasma glucose (FPG), HbA1c, and serum LFTs (AST, ALT, ALP, total proteins, albumin, and bilirubin) were measured in addition to serum lipids.Results: T2DM patients exhibited significantly higher FPG, HbA1c, AST, and ALT mean values than the controls. Serum aminotransferases were increased in 30% of patients. Serum albumin and total bilirubin (TSB) decreased in 18.6 and 37.2% respectively. Diabetics with HbA1c>7.0% had significantly higher AST, ALT, ALP, and STP values and lower serum albumin and TSB. The logistic regression analysis revealed that duration, BMI, HbA1c, and age are independent co-variables significantly linked to increased ALT activity. Conclusions: LFTs (mainly aminotransferases) are altered in DM. The duration of diabetes, the age of the patient, BMI, and glycemic control influence this change. We recommend monitoring LFTs in DM and maintaining good glycemic control.
Keywords: Humans; Transaminases; lidé středního věku; Blood Chemical Analysis; Liver Function Tests; Female; jaterní testy; Aged; dospělí; senioři; lidé; Diabetes Mellitus, Type 2; Adult; transaminasy; ženské pohlaví; Male; Middle Aged; biochemická analýza krve; mužské pohlaví; diabetes mellitus 2. typu; glykovaný hemoglobin; Glycated Hemoglobin